Literasi Keuangan Digital: Bahaya dan Dampak Pinjaman Online Ilegal Bagi Mahasiswa Studi Kasus Semester 1 Fakultas Ekonomi dan Bisnis Universitas Negeri Gorontalo - Valentina Monoarfa; Aminarti Daud; Noviyanti Fatimah Riyadi; Niluh Gede Julianti; Karsum Yahya; Hadija Laima; Nuranisa Lakoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The rapid development of digital technology has given rise to various new innovations, including online loans. Illegal online loans have become a serious problem in Indonesia, especially in Gorontalo. However, on the other hand, illegal online lending practices have also emerged which are detrimental to consumers, especially students. This research aims to find out how many students at Gorontalo State University are familiar with online loans. The method used in this research uses a descriptive qualitative approach. The results of this research show that many students are familiar with online loans and many have even used illegal online loans. Based on data, students have a fairly good understanding of online loans. They realize that illegal online loans offer easy access and fast processing, it is very common for social media users to receive offers or advertisements for illegal online loans. These ads often appear on homepages, in the form of paid posts, or even direct messages, but they also come with risks that you need to be aware of.